2016
DOI: 10.1002/poi3.123
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Digital Desert in Sub‐Saharan Africa: Does Policy Matter?

Abstract: The last decade has seen a rapid growth of Internet access across Africa, although it has not been evenly distributed. It is therefore important for policymakers to ask how policy can bridge this inequality of Internet access. This article addresses the dearth of research assessing the interplay between policy and Internet penetration by identifying Internet penetration‐related policy variables and institutional constructs in Sub‐Saharan Africa. Based on a literature review and data availability, four variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…One conventional policy measure would be to impose tax incentives both to stimulate online usage and to stimulate local online service production. As shown in Wentrup, Xu, Nakamura, and Ström (2016), lowered tax on import of computer equipment is positively related to Internet penetration in Sub-Saharan Africa; hence, by lowering such tax one could expect to spur more online usage and, eventually, online production on emerging markets. Furthermore, a fair tax regime for international OSPs in local markets is an urgent policy to put in place (OECD, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One conventional policy measure would be to impose tax incentives both to stimulate online usage and to stimulate local online service production. As shown in Wentrup, Xu, Nakamura, and Ström (2016), lowered tax on import of computer equipment is positively related to Internet penetration in Sub-Saharan Africa; hence, by lowering such tax one could expect to spur more online usage and, eventually, online production on emerging markets. Furthermore, a fair tax regime for international OSPs in local markets is an urgent policy to put in place (OECD, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Online presence of large OSPs in international markets should be balanced with either financial compensation or offline presence in order to foster a more regionally diversified OSP economy. Wentrup, Xu, Nakamura, and Ström (2016) found that the universal service policy and its fund are efficient measures to stimulate online usage in Sub-Saharan Africa. Such measures directly address the inequalities of online usage between regions or social groups and are a good example of how to drive towards a more inclusive online economy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, infrastructural weaknesses are identified as a major barrier to digital entrepreneurship in the global South (Quinones et al 2015; see also Damarillo 2011), and as a major differentiator of digital economies in developed and developing economies. These must be overcome in order for the promise of digital economies to be fully realised and to avoid the current situation of what Wentrup et al (2016) call "black holes of information capitalism". This becomes all the more imperative due to other trends; for example, the growing urbanisation of developing country populations (it is anticipated that by 2030 urban populations will have grown to around five billion people (Marcus et al 2015)); and the increasing data-intensity of economic processes alongside the affordances of cloud computing and the Internet of Things (Greengard 2010, Hilbert 2016.…”
Section: Digital Infrastructure Challengesmentioning
confidence: 99%
“…For example, Wentrup et al (2016) discovered that digital policy instruments such as the active level of using universal service funds and low level of tax on computer equipment are significantly correlated with internet access in the 46 countries in SubSaharan Africa. Particularly in developing public services, the involvement of the government and public authorities is self-evident.…”
Section: Reviewing Contextual Components Of Information Technologiesmentioning
confidence: 99%